Monetary policy in a channel system - Aleksander Berentsen; Cyril Monnet (Center for Economic Studies and ifo Institute (CESifo), 2007)
Channel systems for conducting monetary policy are becoming increasingly popular. Despite their popularity, the consequences of implementing policy with a channel system are not well understood. We develop a general equilibrium framework of a channel system and investigate the optimal policy. A novel aspect of the channel system is that a central bank can tighten or loosen its policy without changing its target rate by increasing the interest-rate spread symmetrically around the target rate. This questions the characterization of optimal policy through interest-rate rules, as done in a large body of the literature on the optimal design of interest-rate rules.
Keywords: E40; E50; D83; 330; monetary policy; interest rates; search; Zinspolitik; Regelgebundene Politik; Geldpolitik; Suchtheorie; Theorie